ANTIBACTERIAL, ANTIOXIDANT AND TOPOISOMERASE-I INHIBITOR ACTIVITIES OF THE COASTAL ETHNOMEDICINAL PLANT Pemphis acidula - Linawati Hardjito (BIOTROPIA, 2007)
Pemphis acidula stem bark had been used traditionally in Indonesia to treat Recurrent Aphthous Stomatitis This research was conducted to examine the biological activities of its extract as antibacterial, antioxidant and topoisomerase-I inhibitor. The latter mentioned is one of the target molecules for anticancer drug. The antibacterial activity was examined using disc diffusion assay against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Streptococcus mutans. The antioxidant activity was measured using superoxide radical scavenging activityassay. Topoisomerase-Inhibitor activity was determined using the method reported by TopoGEN. The chloroform extract did not show antibacterial activity and it has low antioxidant activity (48.5%). The ethyl acetate and methanol extracts positively inhibited the growth of target bacteria at concentration of 0.3-mg/paper disk. It also showed high antioxidant activity. At concentration of 250 µg/ml both extracts were able to scavenge superoxide free radicals which was 94.8% and 83.4% for ethyl acetate and methanol extract, respectively. The methanol extract also inhibited topoisomerase-I activity at concentration of 7.5 µg/ml. The results suggest that there is a correlation between antibacterial, antioxidant and topoisomerase-I inhibitor activity. The stem bark extracts contain biologically active compounds that could be potential for nutraceutical or pharmaceutical development.